Why teach or learn about the Holocaust? Teaching aims and student knowledge in English secondary schools. Issue 3 (3rd July 2017) - Pettigrew, Alice
ABSTRACT: This article explores relationships between teaching aims and student knowledge and understanding of the Holocaust in discussion of selected findings from two large-scale empirical studies conducted in English secondary schools. It draws on the work of educational theorists Gert Biesta and Michael Young in order to extend and expand upon the dominant, dichotomizing discourse of "historical versus non-historical" approaches within which much existing Holocaust education literature has previously been framed. Following Young, the article asks: What forms of knowledge of the Holocaust are most "powerful" in terms of facilitating student understanding? And further: Which teaching aims are best suited to ensuring all students have access to these?